P67L: a cystic fibrosis allele with mild effects found at high frequency in the Scottish population - Gilfillan, A; Warner, J P; Kirk, J M; Marshall, T; Greening, A; Ho, L P; Hargreave, T; Stack, B; McIntyre, D; Davidson, R; Dean, J C; Middleton, W; et al. (Journal of medical genetics, 1998)
Only three mutant cystic fibrosis (CF) alleles have to date been established as conferring a dominant mild effect on affected subjects who are compound heterozygotes. We now add a fourth, P67L, which occurs on about 1.4% of Scottish CF chromosomes. Among 13 patients (12 unrelated) with this allele, the average age at diagnosis was 22.5 +/- 11.3 years. None of the cases had consistently raised sweat chloride concentrations, the average value being 57 +/- 9 mmol/l; 77% of the patients were pancreatic sufficient. When compared to three other established mild CF alleles, R117H, A455E, and 3849 + 10kb C-T, a compound heterozygote for P67L has minimal disease and clinical suspicions are unlikely to be confirmed other than by DNA typing.